Progress in the study of oxidative stress damage in patients with schizophrenia: challenges and opportunities - Zhang, Kaiguo; Zou, Lijing; Cai, Yi (Frontiers in Psychiatry, 2025)
Schizophrenia is a serious psychiatric disorder of multifactorial triggers, with a lifetime prevalence of about 1% in all countries of the world, with a slightly higher prevalence in males than in females, and with a peak incidence between the ages of 15-35 years old, and a poor prognosis for most of the patients, which imposes a heavy burden on the society and the family. Early intervention is important for the prognosis and regression of patients. More and more studies have found that the imbalance of oxidation and antioxidant, and the persistent damage to the brain by oxidative stress play an important role in the occurrence and development of schizophrenia. Antioxidants, as additive therapy, play an important role in improving symptoms as well as preventing relapse in patients with schizophrenia. This paper intends to address the pathogenesis of oxidative stress injury and schizophrenia, and the significance of oxidative stress in the treatment of schizophrenia.